Nurses\' Level of Awareness and Observance of Patients\' Rights - Fatemeh Sookhak; Mohammad Rafi Bazrafshan; Alireza Ahmadi; Esmaeil Kavi (Iran University of Medical Sciences, 2019)
Background: Patient's rights as one of the basic pillars in defining the standards of clinical services indicate that the patient's biopsychosocial and spiritual needs are met in the form of standards, rules, and regulations. This study aimed to evaluate the level of awareness and observance of patients' rights by nurses working in hospitals affiliated to Larestan University of Medical Sciences. Methods: In this descriptive cross-sectional study, 83 clinical nurses were recruited by convenience sampling method. To collect the research data, researcher-made questionnaires, including Patient's Rights Awareness and "Patient's Rights Observance were used. The reliability of the two parts of the questionnaire was reported using Cronbach's alpha coefficients as 0.51 and 0.69, respectively. The obtained data were analyzed in SPSS using descriptive and Chi-squared tests.  Results: The knowledge of patient rights was poor, moderate, and good in 81.9%, 16.9%, and 1.2% of the nurses, respectively. Additionally, nurses' performance regarding patients' rights was reported as moderate in 83.1%, poor in 13.3%, and good only in 3.6% of them. Chi-squared test results revealed that among the demographic variables, only gender and education were significantly correlated with the knowledge and practice of nurses regarding the observance of patients' rights (P<0.05). Conclusion: The study participants' knowledge of patients' bill of rights was poor, and their observance of patients' rights was moderate; thus, interventions should be performed to prevent the violations of patients' rights. Continuing education programs and in-service training about the observance of the patients' bill of rights should be considered more seriously.